Combining motivational interviewing and cognitive behavioural therapy for the treatment of adolescent substance abuse : a multiple-baseline across participants study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, at Massey University - Jory, Anna Marguerita Maureen (Massey University, 2003)
The overall goal of the present research was to investigate whether a standardised integration of motivational interviewing (MI) and cognitive-behavioural therapy (CBT), adapted to work specifically with this population, could be effective in treating substance use disorders in New Zealand adolescents. The present study examined the efficacy of utilising a brief (eight-ten session) combined MI and CBT treatment manual (Vilke & Ronan, 2002) with three adolescent males diagnosed as having substance abuse or dependence disorders (American Psychological Society, 1994). Treatment was carried out in participants schools. A single-case, multiple-baseline across participant's experimental design was employed, with 18-day, 25-day and 30-day baselines being used. Pre-treatment, post-treatment, and follow-up assessment consisted of a diagnostic interview and a battery of measures which assessed drug and alcohol use (type, frequency, duration), related emotional, behavioural and psychological problems, level of involvement with substances, attitudes towards drugs and alcohol, problem severity, risk factors, and relapse coping skills. Weekly measures also assessed participants' readiness to change their drinking and drug use behaviour, and their perceived benefits of drinking and drug use. Participants also kept daily substance use diaries throughout baseline and treatment and for one week at ten weeks post-treatment. Participants' weekly measures and daily substance use were assessed using a multiple-baseline visual inspection. Other measures were analysed for clinical significance. Results indicated that while the intervention did not result in the participants becoming abstinent, it was successful in changing substance use behaviour, resulting in all participants reducing their cannabis use and participant 1 substantially reducing his other substance use. The intervention also increased participants' coping and relapse prevention skills, and reduced their perceived benefits of drinking and drug use. The limitations to this study and a wide range of areas that still need further investigation in relation to the treatment programme are discussed. Overall, what this research has highlighted is that the structured intervention developed for use in the present study is worthy of further research. Randomised controlled trials are now needed to determine if the programme is effective with a wider range of adolescents, and to ascertain which components of the intervention are the most critical.
Keywords: Cognitive therapy for teenagers; Teenagers' substance abuse; Substance abuse treatment; Adolescent substance abuse